PENGARUH TAX PLANNING, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022 - Marisa Nuraeni, Siti (Jurnal Nusa Akuntansi, 2024)
This study aims to determine the influenceof Tax Planning, Dividend Policy and debt policy on company value in property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. This type of research is quantitative secondary data obtained from the Indonesia Stock Exchange (BEI) and the website of each company. The analysis technique used in the research used purposive sampling, with a sample size of 40 data from 8 companies with observations for 5 years 2018-2022. The results of this research show that Tax Planning, dividen policy and debt policy simultaneously have an effect on company value, and tax planning dividend policy partially do not have a effect on company value while debt policy partially has a significant effect on company value